Respuesta :

Answer:

The explicit formula for the given expression is [tex]a_n=-10+3n[/tex].

Step-by-step explanation:

The given sequence is

-7, -4, -1, 2, 5

The difference between two consecutive terms is same, therefore the given sequence is an arithmetic sequence.

The first term of the given AP is -7 and the common difference is

[tex]-4-(-7)=-4+7=3[/tex]

The explicit formula for an AP is

[tex]a_n=a+(n-1)d[/tex]

Where, a is first term, d is common difference and n is number of terms.

Substitute a=-7 and d=3 in the above equation.

[tex]a_n=-7+(n-1)3[/tex]

[tex]a_n=-7+3n-3[/tex]

[tex]a_n=-10+3n[/tex]

Therefore the explicit formula for the given expression is [tex]a_n=-10+3n[/tex].

Answer:

an = -7 + (n - 1) 3

Step-by-step explanation: